Extreme climatic events shape arid and semiarid ecosystems. Issue 2 (1st March 2006) - Holmgren, Milena; Stapp, Paul; Dickman, Chris R.; Gracia, Carlos; Graham, Sonia; Gutiérrez, Julio R.; Hice, Christine; Jaksic, Fabián; Kelt, Douglas A.; Letnic, Mike; Lima, Mauricio; López, Bernat C.; et al.
Abstract : Climatic changes associated with the El Niño Southern Oscillation (ENSO) can have a dramatic impact on terrestrial ecosystems worldwide, but especially on arid and semiarid systems, where productivity is strongly limited by precipitation. Nearly two decades of research, including both short‐term experiments and long‐term studies conducted on three continents, reveal that the initial, extraordinary increases in primary productivity percolate up through entire food webs, attenuating the relative importance of top‐down control by predators, providing key resources that are stored to fuel future production, and altering disturbance regimes for months or years after ENSO conditions have passed. Moreover, the ecological changes associated with ENSO events have important implications for agroecosystems, ecosystem restoration, wildlife conservation, and the spread of disease. Here we present the main ideas and results of a recent symposium on the effects of ENSO in dry ecosystems, which was convened as part of the First Alexander von Humboldt International Conference on the El Niño Phenomenon and its Global Impact (Guayaquil, Ecuador, 16–20 May 2005).